2007
DOI: 10.3758/bf03193757
|View full text |Cite
|
Sign up to set email alerts
|

Nonspatial attributes of stimuli can influence spatial limitations of attentional control

Abstract: Work from a variety of approaches suggests that the selection and representation of visual information is subject to fairly severe spatial limitations. These limitations are believed to reflect the structure and function of basic visual information-processing mechanisms, including the formation and individuation of coherent object representations (see, e.g., Cavanagh, 2001; C. W. Eriksen & Hoffman, 1973;He, Cavanagh, & Intriligator, 1996Intriligator & Cavanagh, 2001;Pelli, Palomares, & Majaj, 2004). Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…In particular, it forces observers to rely on spatial location more than they might if the items differed in other attributes as well (e.g., color). Consistent with this possibility, we have found that attentional walks can be executed more reliably in dense arrays when the disks are heterogeneously colored than when they are identical (Moore, Lanagan-Leitzel, Chen, Halterman, & Fine, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…In particular, it forces observers to rely on spatial location more than they might if the items differed in other attributes as well (e.g., color). Consistent with this possibility, we have found that attentional walks can be executed more reliably in dense arrays when the disks are heterogeneously colored than when they are identical (Moore, Lanagan-Leitzel, Chen, Halterman, & Fine, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…could conduct an attentional walk from red item to red item, thereby effectively halving the density of the display. If, however, performance in the walk task does not reflect attention being allocated within an organized representation of the display but, instead, depends only on the local (image level) distinctiveness of items, then, although there may be some advantage for the organized display over a completely homogeneous array, similar to that found by Moore et al (2007), it is unlikely that it would effectively halve the display density.…”
mentioning
confidence: 78%
“…In an earlier study (Moore et al, 2007), we showed that performance in the attentional walk task is better when the array in which the attentional walk occurs consists of heterogeneously colored disks than when it consists of identical (gray) disks. Note that this would not be expected if the walk task reflected only limitations of attentional resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The density of the array is varied from sparse, where reliable shifts of attention are easily achieved, to dense, where reliable shifts of attention are difficult or impossible. Previous work has shown that performance in the attentional walk task reflects limitations in the precision with which attention can be localized within an array of items (Moore, Lanagan-Leitzel, Chen, Halterman, & Fine, 2007;Moore, Lanagan-Leitzel, & Fine, 2008). In particular, rather than reflecting only the spatial resolution of selection, which can be thought of as the size of the metaphoric spotlight of attention (Cave & Bichot, 1999), it seems to reflect the spatial uncertainty with which attention can be focused, which can be thought of as the tremor, so to speak, that occurs while the metaphoric spotlight is moved from one point of focus to another.…”
mentioning
confidence: 99%